Asymmetric MoS2/Graphene/Metal Sandwiches: Preparation, Characterization, and Application. Issue 37 (27th July 2016) - Toth, Peter S.; Velický, Matĕj; Bissett, Mark A.; Slater, Thomas J. A.; Savjani, Nicky; Rabiu, Aminu K.; Rakowski, Alexander M.; Brent, Jack R.; Haigh, Sarah J.; O'Brien, Paul; Dryfe, Robert A. W.
Abstract : The polarizable organic/water interface is used to construct MoS2 /graphene nanocomposites, and various asymmetrically dual‐decorated graphene sandwiches are synthesized. High‐resolution transmission electron microscopy and 3D electron tomography confirm their structure. These dual‐decorated graphene‐based hybrids show excellent hydrogen evolution activity and promising capacitance performance.